Experimental & CFD Investigation of Cooling Performance of Mini-Channel Heat Sink using Nanofluid (Al2O3-H2O) - Thakur, Rohit (My University, 2015)
Efficient heat transfer has become major need these days. In this thesis, both experimental and CFD investigations have been carried out to evaluate the cooling performance of a mini-channel consisting of two different cross- sectional shapes of rectangular and triangular. Three different working fluids consisting of water, 0.01% vol. conc. Al2O3-H2O nanofluid and 0.05% vol. conc. Al2O3-H2O nanofluid are used Investigation is carried out at three different flow rates, 30LPH, 90 LPH and 150 LPH. Heating element of 130 W capacity is used to heat up the heating element. From both experimental and simulated results, it is seen that better cooling performance is seen with nanofluid as compared to water, for both cross-sectional shapes of mini-channel (triangular and rectangular). Also with increasing vol. concentration, better cooling performance of mini-channel is also reported. With 0.05% vol. conc. Al2O3-H2O nanofluid around 0.08233 kJ and 0.07953 kJ of heat is removed from rectangular and triangular cross-sections of mini-channels respectively. Rectangular shaped cross-section of the mini-channel has shown better cooling performance as compared to triangular cross-section of mini-channel, with same working fluid and at a same flow rate, as better heat transfer rate is seen for rectangular shape as compared to triangular cross-section shape of mini-channel. Both experimental and CFD simulated results are in close agreement with a difference of 12%.
ME, MED
Keywords: Heating; Cooling; Nano-fluid; Heat Sink; MED